Identification of barley genotypes with high antioxidant activity - Narwal, Sneh; Kumar, Dinesh; Verma, Ramesh Pal Singh; Sharma, Indu (Journal of Cereal Research, 2014)
Antioxidant activity is a very important characteristic of the cereal grains like wheat and barley. Barley genotypes with higher antioxidant activity can be beneficial both as food and also in brewing. A barley crossing block with 265 lines was screened for the antioxidant activity using two antiradical methods. Using both the methods, the line Kasota showed significantly high antioxidant activity. Multilocation trials in the subsequent year also showed that this line has high antioxidant activity as compared to the check and one more line used. Identification of the barley lines with higher antioxidant activity can help the breeding programme in developing food and malt barley varieties with higher antioxidants and better health and industrial benefits. Â